A Computer Comparison of Four Quadratic Programming Algorithms - Braitsch, Raymond J. (Management Science, 1972)
This paper compares the computational performance of the quadratic programming algorithms of Dantzig, Beale, Wolfe and a modification of Wolfe's algorithm. Problems are generated and solved on the computer with iteration count serving as the principal method of comparison. The effect of certain problem parameters on rate of convergence is considered and computer time and storage requirements of the four algorithms are discussed.